Impact of Mobile Banking on Financial Performance of Unguka Microfinance Bank Ltd, Rwanda (Global Journal of Management and Business Research, 2017)
Abstract not found
Keywords: mobile banking; financial performance; microfinance; profitability; revenue and liquidity